Ligands of Diltiazem Binding Site: An Overview of Some Chemotypes - Budriesi, R.; Ioan, P.; Carosati, E.; Cruciani, G.; Zhorov, B. S.; Chiarini, A. (Mini Reviews in Medicinal Chemistry, 2009)
The diltiazem binding site of L-type calcium channels is the least characterized to date. In this paper, we present some of the available chemotypes that bind to the benzothiazepine binding site: natural compounds, compounds synthesized by varying the benzothiazepine scaffold, and compounds discovered by means of computational approaches.
Keywords: chemotype